A Classification of Fourth-Order Dissipative Differential Operators. (21st January 2020) - Wang, Tao; Ao, Ji-jun; Yang, Mei-chun
Abstract : This paper is devoted to the classification of the fourth-order dissipative differential operators by the boundary conditions. Subject to certain conditions, we determine some nonself-adjoint boundary conditions that generate the fourth-order differential operators to be dissipative. And under certain conditions, we prove that these dissipative operators have no real eigenvalues.